2005
DOI: 10.1080/00365520410009302
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer confined to the muscularis propria: A possible candidate for laparoscopic surgery or adjuvant therapy

Abstract: Lymph node metastasis is the only significant risk factor of mp cancer. Patients with lymphatic metastasis should undergo postoperative adjuvant therapy. On the other hand, patients with mp cancer without lymph node involvement have an excellent prognosis and could be candidates for laparoscopic gastric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 13 publications
0
17
0
3
Order By: Relevance
“…Clinical T1 cancer with perigastric LN involvement and serosa-negative gastric cancer without LN metastasis are also regarded as expanded indications for the use of MIS 4,5,13,14. These specific groups of patients could be treated in randomized controlled trials comparing different approaches.…”
Section: Indication Of Mis For Gastric Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical T1 cancer with perigastric LN involvement and serosa-negative gastric cancer without LN metastasis are also regarded as expanded indications for the use of MIS 4,5,13,14. These specific groups of patients could be treated in randomized controlled trials comparing different approaches.…”
Section: Indication Of Mis For Gastric Cancermentioning
confidence: 99%
“…Therefore, the results of treating advanced cancer with MIS should be investigated. Although there is no evidence and there are no guidelines that indicate that the use of MIS is appropriate, even for EGC, experienced surgeons have begun to treat patients with AGC using MIS, and have reported acceptable short-term outcomes 2,4,5,15,37,38. For some selected AGC cases, surgeons believe that this approach is not inferior to open conventional surgery in terms of the oncologic aspects.…”
Section: Mis For Agcmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of laparoscopic surgery under CO2 pneumoperitoneum on the recurrence or progression of AGC are unknown. Park et al [25] found, by clinicopathological examination, that gastric cancer without lymph node metastasis (N0) and confined to the muscularis propria had an excellent prognosis and could be treated with LADG. Several recent reports from Japan and Italy describe good long-term outcomes after LADG for AGC (T2N0) [26,27].…”
Section: Advanced Gastric Cancer (Agc)mentioning
confidence: 99%
“…Initial indications for robotic gastrectomy were early gastric cancers without evidence of lymph node metastasis based on clinical diagnosis. It was expanded to include clinical stage T1‐2 cancers with or without perigastric lymph node metastasis, except for lesions for which endoscopic submucosal dissection (ESD) was indicated 8, 9. So far, in Korea and Japan, neither robotic nor laparoscopic gastrectomy is indicated for the treatment of serosa‐involved advanced gastric cancer 10.…”
Section: Indications Of Robotic Applicationmentioning
confidence: 99%